Atypical HUS due to factor H antibodies in an adult patient successfully treated with eculizumab. (August 2014) - Green, Hefziba; Harari, Emanuel; Davidovits, Miriam; Blickstein, Dorit; Grossman, Alon; Gafter, Uzi; Gafter-Gvili, Anat
Abstract Background: Anti-complement factor H (CFH) antibodies is an extremely rare cause of atypical hemolytic uremic syndrome (aHUS) in adults, with less than 10 cases reported thus far. Although infectious diarrhea is a common inciting trigger for aHUS episode, there are no reports of an association with inflammatory bowel disease. Eculizumab is an emerging treatment for aHUS. Eculizumab has not been reported thus far to be given for aHUS due to anti-CFH antibodies. We report here for the first time on an adult patient with ulcerative colitis (UC) who developed aHUS due to anti-CFH antibodies, presented with decreased serum levels of both C3 and C4. She had an excellent response to treatment with eculizumab. Case presentation: A 27-year-old Caucasian woman, who suffered from steroid-dependent UC, was admitted with microangiopathic hemolytic anemia and acute kidney injury with nephrotic syndrome. ADAMTS 13 was normal and comprehensive workout for secondary causes of HUS was negative. Both serum complement level of C3 and C4 were low. Kidney biopsy was compatible with the diagnosis of HUS with negative immunofluorescence. Because of only partial response to plasma exchange and high dose steroids, eculizumab was commenced. After two weeks signs of microangiopathy subsided, and kidney function began to recover. Few months after the diagnosis, a complement components investigation revealed antibodies against CFH at high titer of 2000 arbitrary units. Today her creatinine is stable with no proteinuria and no signs of HUS.